Ստուգաբանություններ - Պետրոսյան, Ա. Ե.
1. Арм. drawš «статуя бога» сопоставляется с урарт. diruši, обозначающего, видимо, статую верховного бога Халди. 2. Арм. kot‘oɫ «монумент, башня» соответствует урарт. qudula-ni «храм, башня», которым обозначались специфические башенные храмы Халди. 3. Урартское личное имя Lubšusini этимологизируется как древне- арм. Lusacin «светородный» / «рожденный светом». 1. Arm. drawš "statue of a god" is compared with Urart. diruši, apparently denoting the statue of the supreme god Haldi. 2. Arm. kot‘oɫ “monument, tower” corresponds to Urart. qudula-ni "temple, tower", which denoted the specific tower temples of Haldi. 3. Urart. personal name Lubšuṣini is etymologized as Arm. lusacin "luminous" / "born of light".
Keywords: Լեզվաբանություն